Staff members' ambivalence on caring for patients with multidrug‐resistant bacteria at their end of life: A qualitative study. Issue 15 (22nd June 2018) - Tiedtke, Johanna M; Stiel, Stephanie; Heckel, Maria; Herbst, Franziska A; Sturm, Alexander; Sieber, Cornel; Ostgathe, Christoph; Lang, Frieder R
Abstract : Aims and objectives: To explore healthcare professionals' personal experiences, feelings and attitudes about caring for hospitalised patients with multidrug‐resistant bacteria in palliative and geriatric care. Background: Working in end‐of‐life care involves at times burdening demands that affect not only healthcare professionals personally but also their actions. It is suggested that multidrug‐resistant bacteria and their consequences for colonised or infected patients in hospitals are among the challenges for all professionals in end‐of‐life care. Little is known about the feelings and experiences of staff members during healthcare activities with regard to these bacteria. Design: A qualitative interview study in two German hospitals. Methods: We interviewed 35 staff members from a German palliative care unit and a geriatric unit about their experiences with multidrug‐resistant bacteria in end‐of‐life care and the management of colonised or infected patients. Semistructured interviews were transcribed verbatim and analysed using grounded theory. Results: Interviewees represented two interdisciplinary teams with 40% nurses, 26% physicians and 34% other professionals. Salient themes that were identified included impact of multidrug‐resistant bacteria on staff members' personal actions, feelings and attitudes towards the bacteria and the required isolation measures. Besides higher workload and consequences for working routines, the patients' palliative care needs were recognised, as well as the necessary protection measures to avoid contaminations in hospital. Healthcare professionals reported a dilemma that they experienced when facing these diverse demands. Conclusions: Findings point to emotional and behavioural ambivalence in end‐of‐life care among staff members because necessary isolation measures and particular situation in end‐of‐life care create unsolvable conflicts for healthcare professionals. Possible strategies to cope with ambivalence are discussed. Relevance to clinical practice: Healthcare professionals in palliative and geriatric care have to deal with multidrug‐resistant bacteria and have to face contradictory feelings while trying to fulfil patients' needs as well as isolation requirements.